An Econometric Model of the Determinants of Married Women’s Land Rights in A1 Resettlement Areas in Zimbabwe - Njaya, Tavonga (Asian Journal of Economic Modelling, 2014)
The study investigated the major determinants of married women’s land rights under the fast track land reform programme, 2000-2002 in A1 resettlement areas in Zimbabwe using econometric analysis on national baseline survey. Case data collected in Goromonzi District through in-depth interviews, direct observations and documentary reviews were used to complement results from the econometric model. Although the focus was on women beneficiaries of the fast track land reform programme, the study adopted a gender approach to study both men and women. The study revealed that extra-household factors such as the method used to make beneficiaries aware about the fast track land reform programme, the size of arable area cultivated and provincial differentials of male and female beneficiaries determined the probability of women’s land holding. This meant that social assets were a strong determinant of women’s land rights and hence the socio-political environment should not be ignored when analysing the distribution of land under the fast track land reform programme. The study recommended that individual level asset ownership data should be collected in order to evaluate and understand how benefits of development programmes are shared between men and women and that allocation of land under the land reform programme should focus on individuals within households. Methods should be devised to inform women about their land rights and the avenues through which these rights can be enforced. A study of each province would be required to unravel the underlying factors for the differential land distribution patterns by sex in provinces.